Air quality in the clinical embryology laboratory: a mini-review - Romualdo Sciorio; Erika Rapalini; Sandro C. Esteves (SAGE Publishing, 2021)
The scope of the clinical embryology laboratory has expanded over recent years. It now includes conventional in vitro fertilization (IVF) techniques and complex and time-demanding procedures like blastocyst culture, processing of surgically retrieved sperm, and trophectoderm biopsy for preimplantation genetic testing. These procedures require a stable culture environment in which ambient air quality might play a critical role. The existing data indicate that both particulate matter and chemical pollution adversely affect IVF results, with low levels for better outcomes. As a result, IVF clinics have invested in air cleaning technologies with variable efficiency to remove particulates and volatile organic compounds. However, specific regulatory frameworks mandating air quality control are limited, as are evidence-based guidelines for the best air quality control practices in the embryology laboratory. In this review, we describe the principles and existing solutions for improving air quality and summarize the clinical evidence concerning air quality control in the embryology laboratory. In addition, we discuss the gaps in knowledge that could guide future research to improve clinical outcomes.